(untitled) - Samuelson, Paul Anthony (New York, 1964)
More than just a historical curiosity, however, this book's power to explain economics to both the expert and the novice shines on every page. As fascinating now as when they were first published in 1948, the wisdom and applicability of Samuelson's words remain vital in today's turbulent economic world
Keywords: Economics